PENGARUH JUMLAH PENDUDUK DAN PDRB TERHADAP KEMISKINAN DI PROVINSI SUMATERA UTARA - Rapika Kesatriani Damanik; Selna Aprilia Sidauruk (Jurnal Darma Agung, 2020)
Poverty is a problem in development. With the existence of poverty, development is hampered. The factors causing poverty include population and GDP. This study aims at determining the effect of population and GDP on poverty in North Sumatra in 2008-2017 so that the bias is used as a basis for determining policies and strategies in overcoming poverty in North Sumatra. The data used in this study is secondary data obtained from the Central Statistics Agency (BPS) while the data analysis technique used in this study is multiple linear regression analysis with the help of SPSS 24. The results show that the population and GRDP had a significant effect on poverty in North Sumatra.